Psychological Type and the Interpretation of Sacred Text: Introducing the Sift Approach to Hermeneutical Theory - Leslie J. Francıs (Dini Araştırmalar)

(untitled)
This study explores the implications of psychological type theory for the interpretation of sacred text. The argument is advanced in two steps. Step one provides a nuanced introduction to psychological type theory in a way designed to assist readers unfamiliar with the theory to assess their own psychological type preference. Step two demonstrates how the SIFT approach to the interpretation of sacred text applies insights from psychological type theory to propose a disciplined way for community engagement with reading and discussing sacred text.